Assistance For Cihanjawar Village UMKM Products Through Business Legality And Packaging In 2023 - Via Parmalasari; Annisa Purwani (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2023)
The Covid-19 pandemic has hit Indonesia and almost in countries around the world, from this incident there are many impacts, one of which is on the community's economic sector, especially on UMKM actors. The impact caused by this incident is a decrease in sales turnover, and a decrease in product sales. In addition, Micro, Small and Medium Enterprises (UMKM) are required to have business legality in order to compete in the global market era. And the legality of the business itself is a business license from an authority for the entire process of establishing a business activity or a sign that a product already has a license and can be circulated, so that consumers do not feel hesitant when they want to buy a product that has been marketed. However, there are still many UMKM actors in the Cihanjawar Village area who do not know and understand the importance of business legality in the form of making a Business Identification Number (NIB), because the local community has an understanding that managing a license and business legality is a complicated and takes a little time. And the Business Identification Number (NIB) itself, is a very important thing for business actors. In addition to the legality of the business, UMKM actors also need to attach importance to product packaging (packaging), because packaging not only functions as a wrapper for a product, but can also facilitate the process of distributing or shipping products to consumers' hands, and product storage so that product quality is maintained, promotional and can attractbuyers. There are several researchers who use the implementation method in this community service activity using the Participatort Action Research (PAR) method. The steps taken by the researcher at the time of service, first making observations in the environment of RT 07 RW 03 Cihanjawar Village, secondly socialization, third presentation of material, fourth practice and assistance. The results of community service that have been carried out include: Increasing the knowledge of UMKM in Cihanjawar Village, especially in RT 07 RW 03 in determining product packaging that aims to attract consumer interest and increase public interest in legalizing the type of business